John Jay Sherman papers - Sherman, John Jay, 1844-1922.
Chiefly letters written by Sherman to his family during his service with the 8th New York Heavy Artillery Regiment, typescript of Sherman's remniscences of the Civil War, and genealogical material pertaining to the Sherman, Clarke (Clark), and Hover (Hoover) families. Includes material pertaining to Sherman's participation in battles in Virginia, capture by Confederate troops, imprisonment on Belle Isle, in Libby Prison and Salisbury Prison, and his parole.
Union Army soldier and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clark family; Hoover family; Sherman family; Sherman family -- Correspondence; United States. -- Army. -- New York Heavy Artillery Regiment, 8th (1862-1865); Belle Isle (Prison); Libby Prison; Salisbury Prison (N.C.); United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Soldiers; Lawyers